PEMBELAJARAN RESPONSIF BUDAYA BERBASIS KEARIFAN LOKAL UN-TUK MENGUATKAN TOLERANSI DAN SIKAP ANTI-PERUNDUNGAN SISWA SEKOLAH DASAR: STUDI MIXED-METHOD - Haniah, St; Yumriani; Amin, Sulvahrul (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This study aimed to examine culturally responsive learning based on local wisdom to strengthen tolerance and anti-bullying attitudes among elementary school students. The local wisdom values integrated into learning were sipakatau, sipakainge, sipakalebbi, and abbulo sibatang, which emphasize mutual respect, reminding one another, honoring differences, and cooperation. This study used a mixed-method approach with an explanatory sequential design. Quantitative data were collected through tolerance and anti-bullying attitude scales administered before and after the intervention, while qualitative data were obtained from observation, student reflection sheets, and semi-structured interviews. The participants were elementary school students who participated in six culturally responsive learning sessions. The quantitative findings showed an increase in tolerance scores from 64.35 to 78.70 and anti-bullying attitude scores from 62.85 to 80.15. Qualitative findings indicated that students became more able to appreciate differences, use respectful language, reject mocking behavior, and support peers who experienced exclusion. The integration of local wisdom made moral values more meaningful because students learned through cultural expressions familiar to their daily lives. The study concludes that culturally responsive learning based on local wisdom can be an effective contextual strategy for strengthening tolerance and anti-bullying attitudes in elementary education.